Active–reactive power approaches for optimal placement of charge stations in power systems. (January 2017) - Wang, Cheng; Dunn, Roderick; Robinson, Francis; Lian, Bo; Yuan, Weijia; Redfern, Miles
Highlights: A new active and reactive power dispatch method for charging station location choosing is proposed. Compare with old charging station location choosing method, the proposed method used in this paper is more accurate. The 2.6% the annual yield above inflation is a good figure for the long term investment. Abstract: Electric Vehicles (EVs) have been suggested as alternatives to conventional vehicles for reducing petrol consumption and carbon dioxide (CO2 ) emissions. When a large number of EVs connect to the grid, they can cause a large amount of power loss. Where to install multiple charge stations in the grid, so as to mitigate losses caused by EVs when providing energy to those EVs, is becoming vitally important. In this paper, a distribution test-network model is described. A new analytical method is proposed, using the stations' cooperation in terms of optimal active and reactive power dispatch as well as power flow analysis for locating the optimal placement of charge stations, so as to reduce power losses. This method is compared with the previously developed current density method for single charge stations using system simulation results. It was demonstrated that the methods proposed in this paper are more accurate than the current density method, and that 17% of the average active power loss can be saved for three different types of load profile. In addition, 27% of the average active power loss was saved by installing two charge stations rather than no charge stations in the test-line. It is shown that this could represent a 2.6% annual yield above inflation for investing in installing and running such charge stations.